Access to knowledge as prelude to a right to the city for the urban poor in Rajshahi, Bangladesh - Walters, Peter (2014)
One of the fundamental prerequisites for a ‘right to the city’ is a level of knowledge about the processes, services and opportunities that can improve the life chances of the poor. A vital source of knowledge in any urban environment is local government, which provides access to essential services including knowledge about education, health, sanitation and emergency services and security of tenure. This paper reports on a research project conducted in the city of Rajshahi in Bangladesh in 2013 designed to better understand how people living in poverty and absolute poverty accessed these necessary services. Three types of community were used in the case study: a poor slum with access to the donor sponsored Urban Program for Poverty Reduction (UPPR) scheme in operation, a poor slum with no such support and a more ‘middle class’ neighbourhood used for comparison. The study found that local political representatives on the city government tightly controlled access to knowledge and services in all cases. This was to the detriment of the poorest slum, which was exploited by its local elected representative. The UPPR slum had a greater access to information and thus voice due to organised local leadership, with a strong role from women. The middle class neighbourhood enjoyed a close and productive relationship with their local member due to high levels of cultural and symbolic capital. The paper concludes by observing that there are particular levels of community cohesion required before poverty alleviation can work. The best intentions of local authorities to improve services and transparency can be futile if political control is not relinquished at the grassroots level and/or the poor are not adequately mobilised and educated about their entitlements and rights.